UPAYA MENINGKATKAN HASIL BELAJAR DENGAN MENGGUNAKAN METODE INDEX CARD MATCH PADA MATA PELAJARAN AQIDAH AKHLAK DI KELAS VII MTS YASPEN MUSLIM - Junia Anora; Yunus Ismail (Jurnal Iqtirahaat, 2022)
This study aims to determine how the role of Islamic religious education teachers in shaping the religious character of students through extracurricular activities Tahfidz Method education character and purpose education national this push researcher for make a learning that can Upgrade results study Aqidah Morals in self participant educate. Besides that push thing  researcher for doing study action this class (PTK ) is want find learning that leaves impression in the heart participant educate in every learning process , because Theory Aqidah Morals that are made Theory learning is understanding , position and type type Asmaul Husna . On learning that has been done by Aqidah teacher Morals class VII, can said not yet succeed if students who have not reach criteria completeness maximum reached 18 people out of 32 people or 72.5%, while successful student  reach criteria completeness maximum there are 14 people or 43.3%. This thing need a the way that can Upgrade results study students . Based on observation evidently problem are in use method unfinished learning  enough interesting attention students . Study Action Class (CAR) using two cycle , cycle first filled with one time meeting . Researcher use tool data collector in the form of test and observation . From the data analysis , it is known that completeness student on cycle I reached 72.5% and cycle II reached 92.5% with difference increase by 20% with total completed student  as many as 28 people. So on cycle II already  reach criteria success so in study